Why is there resistance to works councils in Germany? An economic perspective. (August 2020) - Müller, Steffen; Stegmaier, Jens
Recent empirical research generally finds evidence of positive economic effects for works councils, for example with regard to productivity and – with some limitations – to profits. This makes it necessary to explain why employers' associations have reservations about works councils. On the basis of an in-depth literature analysis, this article shows that beyond the generally positive findings, there are important heterogeneities in the impact of works councils. The authors argue that those groups of employers that tend to benefit little from employee participation in terms of productivity and profits may well be important enough to shape the agenda of their employers' organization and have even gained in importance within their organizations in recent years. The authors also discuss the role of deviations from profit-maximizing behavior like risk aversion, short-term profit-maximization and other non-pecuniary motives, as possible reasons for employer resistance.